Pengaruh Technical Skills Dan Interpersonal Skills Terhadap Perceived Job Performance Dengan Organizational Commitment Sebagai Variabel Moderasi: (Studi Pada Konsultan Pajak Di Wilayah Jateng Dan Daerah Istimewa Yogyakarta) - Nindi Anggi Wardani; Eka Satria Wibawa (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
This study aims to analyze and explain the effect of technical skills and interpersonal skills on perceived job performance with organizational commitment as a moderating variable (study of tax consultants in Central and DIY regions). The sample is 150 tax consultants in Central Java and DIY with the data analysis technique is PLS SEM. Based on the results of the discussion, the following conclusions can be drawn (1) There is an influence of technical skills on perceived job performance, (2) There is no effect of interpersonal skills on perceived job performance, (3) There is an influence of organizational commitment on perceived job performance, (4) Organizational commitment cannot moderate the influence of perceived job technical skills performance, (5) Organizational commitment can moderate the influence of interpersonal skills on perceived job performance.